1983
DOI: 10.1116/1.572127
|View full text |Cite
|
Sign up to set email alerts
|

Electrical, structural, and bonding changes induced in silicon by H, Ar, and Kr ion-beam etching

Abstract: A study to elucidate the role of processing-induced changes in Si, subjected to ion-beam etching has been made. It is shown that these changes can be related to the primary ion beam used in ion-beam etching. Using ESR, trivalently bonded Si has been shown to be present. Fe and Cr have been found to be the main contaminants. An annealing study revealed that the damage can be annealed out at relatively high temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…This result agrees with those obtained by Fonash et al 2,10 The ion bombardment of the Si surface by inert gas leads to formation of donorlike defects such as trivalently bonded Si atoms. Positive charges present in the defects bring about an increase in the downward bending of the Si band edges adjacent to the surface.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This result agrees with those obtained by Fonash et al 2,10 The ion bombardment of the Si surface by inert gas leads to formation of donorlike defects such as trivalently bonded Si atoms. Positive charges present in the defects bring about an increase in the downward bending of the Si band edges adjacent to the surface.…”
Section: Discussionsupporting
confidence: 92%
“…For H 2 plasma exposure, an a-Si:H film with very large resistivity was presumably formed. 2 The postcleaning treatment was carried out in order to remove the damage layer and/or the insulating film formed during plasma exposure. The first HF dipping removes a natural oxide or an insulating film on the Si surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments made with photoconductive antennas and metal semiconductor contacts based on GaAs demonstrated that an increase in the strength of the electric field leads to an enhanced THz emission (). Furthermore it is widely known that ion and electron beam induced deep defects lead to a shift of the Fermi level toward the middle of the bandgap due to majority carrier trapping . Increasing the defect density will result in an enhanced shift until—when the defect concentration comes close to the majority carrier density—Fermi level pinning at the defect energy level occurs.…”
Section: Resultsmentioning
confidence: 99%
“…However, the pressure dependence of Schottky barrier modification reveals that metallic impurity contamination is not responsible for the degraded rectifying properties of Schottky diodes fabricated on sputter-etched n-Si. In studying the electrical, structural and bonding changes induced in Si by low-energy H, Ar and Kr ion beam etching, Singh et al 35 observed that Fe and Cr from their gas sources were the main impurity contaminants. They showed further that the rectifying qualities of SBDs fabricated on ion beam-etched Si were not metal impurity-related but were rather determined by intrinsic defects.…”
Section: Discussionmentioning
confidence: 99%